Advertisement Remove all ads

Show That: Sqrt((1-cos"A")/(1+Cos"A"))=Cos"Eca - Cota" - Geometry

Sum

Show that: 

`sqrt((1-cos"A")/(1+cos"A"))=cos"ecA - cotA"`

Advertisement Remove all ads

Solution

LHS = `sqrt((1-cos"A")/(1+cos"A"))`

 

 LHS = `sqrt((1-cos"A")/(1+cos"A")xx (1-cos"A")/(1-cos"A"))`

 

 LHS = `sqrt(((1-cos"A")^2)/(1-cos^2"A"))`

 

=`sqrt(((1-cos"A")^2)/sin^2"A")`  ....(sin2A =1- cos2A)

 

 LHS = `sqrt(((1-cos"A")/sin"A")^2)`

 

 LHS = `(1-cos"A")/sin"A" = 1/sin"A" + cos"A"/sin"A"`

 

 LHS = `cos"ecA"-cot"A"` = RHS

Hence Proved

Concept: Application of Trigonometry
  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×